Evaluation of peripheral and autonomic neuropathy among patients with newly diagnosed impaired glucose tolerance - İŞAK, BARIŞ; TANRIDAĞ, TÜLİN (WILEY, 2008)
Background We have aimed to investigate the presence of peripheral and autonomic neuropathy in individuals who had been diagnosed with impaired glucose tolerance (IGT) on the basis of an oral glucose tolerance test, by comparing with age-matched healthy subjects with an oral glucose tolerance test (OGTT) in normoglycernic ranges. Material and methods Conventional nerve conduction studies, heart rate variation variability, heart rate response to deep breathing, heart rate response blood pressure response to standing up quickly, hand to valsalva maneuvre, grip test and sympathetic skin response tests were used to evaluate the IGT and the control subjects. Results No obvious statistical difference indicating peripheral neuropathy and/or cardiac autonomic neuropathy was detected between patient group and controls. Amplitudes of sympathetic skin response of two limbs (right upper and lower extremities) were lower in the IGT patient group when compared to healthy controls (p < 0.05) indicating the presence of sudomotor autonomic neuropathy. Conclusion Complaints and neurological examinations of patients with IGT were thought to be consistent with small-fiber neuropathy in the early phase of glucose intolerance. Not detecting any neuropathic findings in conventional electroneurography should be attributed to insufficient time allowed for settling down of large-fiber neuropathy. Obtaining no response in some of the patients in addition to general decrease in the amplitudes of sympathetic skin responses indicates that sudomotor fibers tend to be affected earlier in autonomic neuropathy in the group with IGT when compared with healthy controls. Newly diagnosed IGT patients take receive priority in primary protection since the time for settling down of cardiac autonomic neuropathy was short. Copyright (c) 2008 John Wiley & Sons, Ltd.
Keywords: impaired glucose tolerance; autonomic neuropathy; peripheral neuropathy; SYMPATHETIC SKIN-RESPONSE; SYMPTOM PROFILE; PREVALENCE; DISEASE; RISK